Fast HPLC method using ion-pair and hydrophilic interaction liquid chromatography for determination of phenylephrine in pharmaceutical formulations - Dousa, Michal; Gibala, Petr (Journal of AOAC International, 2010)
A rapid procedure based on a direct extraction and HPLC determination with fluorescence detection of phenylephrine in pharmaceutical sachets that include a large excess of paracetamol (65 + 1, w/w), ascorbic acid (5 + 1, w/w), and other excipients (aspartame and sucrose) was developed and validated. The final optimized chromatographic method for ion-pair chromatography used an XTerra RP18 column, 3 microm particle size, 50 x 3.0 mm id. The mobile phase consisted of a mixture of acetonitrile and buffer (10 mM sodium octane-1-sulfonate, adjusted with H3PO4 to pH 2.2; 200 + 800, v/v), with a constant flow rate of 0.3 mL/min. The separation was carried out at 30 degrees C, and the injection volume was 3 microL. Fluorescence detection was performed at excitation and emission wavelengths of 275 and 310 nm, respectively. The mobile phase parameters, such as the organic solvent fraction (acetonitrile) in mobile phase as an organic modifier, the concentration of sodium octane-1-sulfonate as a counter-ion, temperature, and pH of mobile phase, were studied. As an alternative to ion-pair chromatography, hydrophilic interaction liquid chromatography (HILIC) was investigated using a Luna HILIC column, 3 microm, 100 x 4.6 mm id. The mobile phase consisted of acetonitrile and buffer (5 mM potassium dihydrogen phosphate, adjusted with H3PO4 to pH 2.5; 750 + 250, v/v) at a flow rate of 0.8 mL/min. The separation was carried out at 25 degrees C, and the injection volume was 5 microL. The proposed method has an advantage of a very simple sample pretreatment, and is much faster than the currently utilized HPLC methods using gradient elution and UV detection. Commercial samples of sachets were successfully analyzed by the proposed HPLC method.
Keywords: farmaceutická chemie; stabilita léku; Phenylephrine; vysokoúčinná kapalinová chromatografie; Limit of Detection; fenylefrin; Chromatography, High Pressure Liquid; limita detekce; Chemistry, Pharmaceutical; Drug Stability